Conversations with myself [compact disc, unabridged] - Mandela, Nelson, 1918-2013 (Macmillan Audio, 2010)
Rising up from political prisoner to become the president of post-apartheid South Africa, Nelson Mandela is often a subject of inspiration. Here, with decades of preparation, Mandela offers his insight on his long captivity, his years as president, and beyond. Part biography, part philosophy, Conversations with Myself gives listeners a once-in-a-lifetime opportunity to delve into the mind and soul of history's most endearing leader.